Analisis kesalahan siswa kelas X agribisnis tanaman perkebunan SMK Negeri 1 Batang Gansal dalam menyelesaikan soal matriks - Ramadhani, Fitri; Saraswati, Mellyani (Mahesa Research Center, 2021)
SMK N 1 Batang Gansal’s students have difficulty learning the matrix material. This can be seen from the result of students who get test scores below score 60. Especially in class x agribusiness plantations 1 with the percentage of daily test scores below score 60, which is 82.6%. Therefore, an analysis is needed to determine the types of errors that students tend to make in solving matrix problems. In this study, data collection was carried out using test and questionnaire methods, with data analysis using descriptive statistics. Based on the data analysis, it was concluded that the mistakes made by students in solving matrix problems were concept errors, principal errors and operational errors, with a tendency for errors in conceptual errors. The causes of errors are not understanding the concepts of matrix material, not listening when the teacher explains the material, not having complete notes or a summary of the matrix material, and not studying the matrix material at home, and not practicing working on various matrix questions so that they are unable to use formulas. matrix well.